PEMAKNAAN LAIN ATAS UTANG PADA IKLAN APLIKASI PINJAMAN ONLINE: STUDI KRITIS SEMIOTIKA DERRIDEAN - Eva Musdalifa (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This research aims to analyze the meaning of debt in Ada Kami online loan advertisements and offer alternative meanings of debt based on netizen responses in the comment column of online loan advertisements. The research uses a critical netnographic approach with analysis based on Derrida's semiotics. The data sources in this research are symbols in online loan advertisements and comments in these advertisements. This semiotic study finds that debt is no longer something that is "embarrassing" but instead becomes a way to support consumerist behavior. Online loans can be a quick and easy solution to obtain a loan when you need urgent funds to meet your needs or desires. Another finding of this research is that debt is not only material but also non-material. The ease of obtaining debt does not guarantee ease afterwards. Debt must consider the values ​​of trust, convenience, security, prudence and spirituality.